Toll-Like Receptor 2 Promoter -196 to -174 Deletion Affects CD4 Levels Along Human Immunodeficiency Virus Infection Progression. - Laplana, Marina; Bravo-Romero, María José; Fernández-Fuertes, Marta; Ruiz-García, Celia; Alarcón-Martín, Emilio; Colmenero Castillo, Juan de Dios; Caruz-Arcos, Antonio; Fibla, Joan; Real-Navarrete, Luis Miguel; Royo-Sánchez-Palencia, José Luis (Oxford Academy, 2020)
Toll-like receptor 2 (TLR2) plays a key role in innate immune response recognizing molecular patterns expressed by pathogens. rs111200466 is a TLR2 promoter insertion/deletion polymorphism with contradictory data about its role in human immunodeficiency virus type 1 (HIV-1) infection. We analyzed rs111200466 in HIV-1 disease progression and showed a correlation with a faster progression to the CD4+ < 200 cells/μL outcome for deletion allele carriers (Cox regression analysis: hazard ratio, 2.4 [95% confidence interval, 1.4–4]; P = .001). When naive patients with CD4+ < 200 cells/μL started antiretroviral treatment, rs111200466-deletion carriers showed a trend toward a slower, recovery rate (time required to reach CD4+ > 350 cells/μL; Cox P = .36). Our data suggest rs111200466 as a prognosis factor for HIV-1 disease progression.
Keywords: Infecciones por VIH; TLR2; polymorphism; HIV infection; rs111200466